Use of geogrid in subgrade-ballast system of railroads subjected to cyclic loading for reducing maintenance - Emeritus, Dean (2021)
During the past twenty-five years biaxial geogrids have been used as reinforcement in the construction of railroad beds and ballasts to improve their performance and structural integrity. A review of several published field and large-scale laboratory test results relating to the reinforcing ability of geogrids is presented. Also included are a number of case histories from several countries where layer(s) of geogrid were used in ballast and sub-ballast layers and on soft subgrade to reduce track settlement and, hence, the frequency of maintenance.